Investigating the Relationship Between Students’ Comprehension of Conversational Implicature and their Levels of Emotional Intelligence in EFL Context. The case of Master one students at M’sila University. - Karima BENTERKI, Meroua HENDI (UNIVERSITE MOHAMED BOUDIAF M'SILA, 2023)
Emotional intelligence has been subject to correlation with numerous academic variables. Its impact stretches beyond the boundaries of the sphere of academia as developing this trait holds a monumental value in individuals’ personal and professional realms. Therefore, the rationale behind the present research is to probe the relationship between students’ comprehension of conversational implicature and their levels of emotional intelligence in the realm of English as a Foreign Language (EFL). To bring about this objective, 30 Master one EFL students at M’sila University were randomly selected to participate in this research, two quantitative data collection instruments were used: the Multiple Discourse Completion Test and the Schutte Self-report Emotional Intelligence Test whereby the former assessed students’ comprehension of conversational implicatures and the latter measured students’ levels of emotional intelligence. The findings revealed a positively moderate and significant correlation between EFL students’ comprehension of conversational implicature and their emotional intelligence (r=.458) at a significance level of (p=0.05). Besides, Pearson’s correlations tests showed that the three subscales of emotional intelligence: perception of emotions, managing own emotions and managing other’s emotions were significantly correlated with the participants’ comprehension of conversational implicature. Consequently, possessing high levels of emotional intelligence plays a facilitating role in comprehending conversational implicature in EFL discourse. It is then advocated that both emotional intelligence training and conversational implicature instruction can be integral parts of EFL classrooms.
Keywords: Conversational Implicature ; Emotional Intelligence ; Correlation ; EFL context.